1999
DOI: 10.1097/00006454-199905000-00002
|View full text |Cite
|
Sign up to set email alerts
|

One dose ceftriaxone vs. ten days of amoxicillin/clavulanate therapy for acute otitis media: clinical efficacy and change in nasopharyngeal flora

Abstract: In an area with a high rate of penicillin-resistant S. pneumoniae, a single dose of ceftriaxone is as efficient as a 10-day course of amox/clav in the treatment of AOM in young children. There was for the two regimens an increased rate of penicillin-resistant strains among the pneumococci carried, whereas the chance for a child to carry a penicillin resistant S. pneumoniae did not increase after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 25 publications
4
32
0
2
Order By: Relevance
“…In~36 % of our subjects, NTHi strains persisted in the NP or middle ear after antibiotic treatment, a finding similar to that of van Schilfgaarde et al (1999) and others (Cohen et al, 1999;Dabernat et al, 1998). Strains that persist in the NP after antibiotic therapy may be the result of antibiotic resistance or other unique characteristics of the strain or could be a consequence of lower levels of antibiotic in a host due to suboptimal absorption of the drug (Pichichero et al, 2008;Pichichero & Reed, 2009).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In~36 % of our subjects, NTHi strains persisted in the NP or middle ear after antibiotic treatment, a finding similar to that of van Schilfgaarde et al (1999) and others (Cohen et al, 1999;Dabernat et al, 1998). Strains that persist in the NP after antibiotic therapy may be the result of antibiotic resistance or other unique characteristics of the strain or could be a consequence of lower levels of antibiotic in a host due to suboptimal absorption of the drug (Pichichero et al, 2008;Pichichero & Reed, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Inc means it was not possible to obtain a sequence for all seven genes for that isolate and therefore the ST was not obtained, but partial analysis clearly allowed us to determine that the strain was different from the other strains in that particular child. MLST types in invasive disease, so we cannot determine whether ST146 and ST685 are associated or not with invasive disease.In~36 % of our subjects, NTHi strains persisted in the NP or middle ear after antibiotic treatment, a finding similar to that of van Schilfgaarde et al (1999) and others (Cohen et al, 1999;Dabernat et al, 1998). Strains that persist in the NP after antibiotic therapy may be the result of antibiotic resistance or other unique characteristics of the strain or could be a consequence of lower levels of antibiotic in a host due to suboptimal absorption of the drug (Pichichero et al, 2008;Pichichero & Reed, 2009).…”
supporting
confidence: 91%
“…55 A single 50-mg/kg dose of ceftriaxone, given either intravenously or intramuscularly, can be used for children who are vomiting, unable to tolerate oral medication, or unlikely to be adherent to the initial doses of antibiotic. [62][63][64] The 3 major bacterial pathogens involved in acute bacterial sinusitis are susceptible to ceftriaxone in 95% to 100% of cases. 56,58,59 If clinical improvement is observed at 24 hours, an oral antibiotic can be substituted to complete the course of therapy.…”
Section: Kas Profilementioning
confidence: 99%
“…This regimen has been shown to be clinically equivalent to standard therapy with amoxicillin, 8,9 cefaclor, 10 trimethoprim/sulfamethoxazole, 11 amoxicillin/clavulanate, 12 and high-dose amoxicillin/clavulanate. 13 However, in 1 large, unpublished trial, 14 standard-dose amoxicillin/clavulanate was shown to be more effective than single-dose ceftriaxone. Despite published evidence supporting single-dose ceftriaxone for the treatment of AOM, obvious disadvantages are the pain, inconvenience, and risk of needle-stick injury associated with use of an injectable agent, and the potential selection of bacterial resistance to a group of agents (cephalosporins) commonly used for the treatment of life-threatening diseases in children.…”
Section: Introductionmentioning
confidence: 99%